Perancangan Meja Laptop Portable Yang Ergonomis Untuk Penyandang Cerebral Palsy Dengan Pendekatan Antropometri - Asfia Fitri Aras; Daumi Rahmatika; Endi Putra (Jurnal INOVATOR, 2019)
Almost all level education have beeb introduced early on as one of the subjects. One of school that has been using a computer or laptop as a medium of learning is a school SLB. Prof. Dr. Sri Soedewi. SLB. Prof. Dr. Sri Soedewi is an extraordinary school of elementary, junior and senior high school students, from all the disorders of blind, deaf, physically disabeld, mentally disabled and Autism. In this study the rspondens werw people with cerebral palsy mixed. That is, people with cerebral palsy accompanied by other symptoms of disease, the person is in a wheelchair, can not do mobility (sitting and standing) without the help of others (in a wheelchair). In the learning process the condition of people with cerebral palsy should be considered. And the facilities provided must be in accordance with the condition of cerebral palsy. Ergonomic portable laptop desk design can be obtained by anthropometry approach in accordance with posture of students of cerebral palsy SLB. Prof. Dr. Sri Soedewi, thus providing comfort, safety and pain relief by using an ergonomic portable laptop desk.